2013
DOI: 10.1364/oe.21.012976
|View full text |Cite
|
Sign up to set email alerts
|

An intense elastico-mechanoluminescence material CaZnOS:Mn^2+ for sensing and imaging multiple mechanical stresses

Abstract: The elastico-mechanoluminescence (EML) properties of CaZnOS:Mn2+ are investigated. The CaZnOS:Mn2+/epoxy resin composite can simultaneously "feel" (sense) and "see" (image) various types of mechanical stress over a wide energy and frequency range (ultrasonic vibration, impact, friction and compression) as an intense red emission (610 nm) from Mn2+ ions. Further, the accurate linear relation between emission intensity and different stress parameters (intensity, energy and deformation rate) are confirmed. The EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 44 publications
4
116
0
Order By: Relevance
“…From Fig. 3, the electronic band structure calculations based on the optimized cell give a direct band gap of 3.895 eV, which is very close to the Therefore, our DFT+U calculation with ab initio-determined Hubbard-U parameters for fully-occupied Zn 3d 10 , as well as the p orbitals for the S and O sites, are self-consistent and reliable, as has also been illustrated in our previous work. 33 -36,52,53,59,78 Fig.…”
Section: Bulk Caznossupporting
confidence: 86%
See 1 more Smart Citation
“…From Fig. 3, the electronic band structure calculations based on the optimized cell give a direct band gap of 3.895 eV, which is very close to the Therefore, our DFT+U calculation with ab initio-determined Hubbard-U parameters for fully-occupied Zn 3d 10 , as well as the p orbitals for the S and O sites, are self-consistent and reliable, as has also been illustrated in our previous work. 33 -36,52,53,59,78 Fig.…”
Section: Bulk Caznossupporting
confidence: 86%
“…The lower conduction band is contributed by the Zn-4s and Ca-3d orbitals. The Zn-3d fully occupied level (3d 10 ) is overlapping with the S-3s filled orbitals and remains in nearly the same energy range, while the O-2s orbital level remains lower. Currently, due to the lack of available valence band X-ray photoemission spectrum data (XPS) for CaZnOS by experiment, we can only compare the qualitative trend result with BaZnOS, which has a similar chemical trend to CaZnOS.…”
Section: Bulk Caznosmentioning
confidence: 99%
“…For undoped CaZnOS, its optical band gap is calculated to be about 3.91 eV, which is in fair agreement with the value of the previously reported. [20][21][22]29,30 Table 3 shows the optical band gap of CaZnOS in previous articles. Fig.…”
Section: 24mentioning
confidence: 99%
“…MZnOS:Mn 2+ (M = Ca, Ba) should be the new and important intrinsic piezoelectric semiconductor systems and have great potential to be used in multifunctional sensor, opticalelectrical integration and coupling devices. In addition, even the ML material CaZnOS:Mn 2+ has been studied by our group for sensing and imaging the multiple mechanical stresses, 17) but to our knowledge the systematical study on the ML properties of MZnOS:Mn 2+ (M = Ca, Ba) has not been reported.…”
Section: +mentioning
confidence: 99%